The Semiotic Construction of Boycott Narratives against Pro-Israel Products: A Case Study of Instagram Account @bdsarabic - Asmawati Safitri; Andi Agussalim; Haeruddin Haeruddin; Fitriani Fitriani (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study investigates the semiotic construction of boycott messages against pro-Israel products on the Instagram account @bdsarabic, situated within the broader discourse of digital activism in the Israeli-Palestinian conflict. As social media platforms increasingly serve as tools of resistance, the Boycott, Divestment, and Sanctions (BDS) movement strategically utilizes Instagram to disseminate political messages. This study aims to explore how visual and textual elements work together to construct symbolic meanings that influence public sentiment and mobilization. Employing a qualitative descriptive method, the research applies Charles Sanders Peirce’s triadic model of semiotics—comprising representamen, object, and interpretant—to analyze three selected campaign visuals targeting Coca-Cola, McDonald’s, and Carrefour. The findings reveal that Arabic texts function not merely as linguistic signs but also as cultural codes that evoke moral and emotional responses. Meanwhile, modified brand logos act as visual arguments, transforming familiar corporate symbols into representations of violence and injustice. The study concludes that such multimodal constructions serve as rhetorical tools to align everyday consumption with ideological resistance. This research contributes to the understanding of how digital platforms, particularly in Arabic-language activist spaces, function as discursive arenas for contesting hegemony and constructing counter-narratives. The findings also offer insights into the role of semiotics in digital communication and the potential of social media as a catalyst for collective consciousness.